ANALYSIS OF THE SEXUAL EXPLOITATION VICTIMS’ RIGHTS FULFILLMENT IN HUMAN TRAFFICKING CRIMES THROUGH THE ROUTINE ACTIVITY THEORY PERSPECTIVE - Anastasya Estin Febyola; Fany N. R. Hakim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Human trafficking (Tindak Pidana Perdagangan Orang—TPPO), which includes sexual exploitation, is a form of organized crime that is on the rise and has serious consequences, particularly for vulnerable groups such as women and children. This study aims to analyze sexual exploitation as the modus operandi in human trafficking and to assess the extent to which the fulfillment of victims’ rights has been implemented, with the focus of the study area at the Kebayoran Baru Police. The research method is a descriptive qualitative approach, with data collected through interviews, observations, and document studies. The findings indicate that economic factors are the primary motivator for victims to become involved in this crime, followed by inadequate parental supervision, a lack of active community involvement, and minimal intervention from law enforcement officers. In terms of fulfilling victims’ rights, the police have implemented protection and assistance measures in accordance with Law Number 21 of 2007 concerning the Eradication of Human Trafficking. However, actual implementation continues to face challenges with regard to institutional coordination and the long-term viability of victim protection.